Explicit and Semi-implicit Complex-Diffusion Schemes for Optical Coherence Tomography Despeckling - Rodrigues, Pedro (2013)
In this paper we illustrate and compare the use of explicit and semi-implicit finite difference schemes for nonlinear complex diffusion with different boundary conditions in the context of medical imaging despeckling, namely for Optical Coherence Tomography images of the eye fundus. Performance metrics are shown to illustrate the feasibility and performance of these numerical schemes.